Perspectives of Islamic Education Students Regarding to Urgency of Technological Skills and Foreign Language Abilility - Wulandari, Viona Dwi; Ramadhany, Nur Fadilah; Lisa, Mona; Neem, Chuti; Sari, Widia Wahana; Mathew, Ingrid Brita Deborah (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2022)
This study aims to analyze the perceptions of students majoring in Islamic religious education towards technological skills and mastery of foreign languages as prospective teachers. This study used a quantitative research method with a survey approach. Data sources were taken using a questionnaire to fifty student respondents as prospective Islamic religious education teachers from four different universities on the island of Sumatra. All were then analyzed descriptively using SPSS software version 20. The results of the analysis showed that; i) in general, respondents agree that technology is a very effective medium in supporting the learning process, in fact, students as prospective teachers must master technology that can be integrated with learning. ii) further related to mastery of foreign languages, as a whole the respondents agreed that mastery of foreign languages for students majoring in teacher training can support their careers as professional teachers, besides that foreign languages are a tool for finding various sources as learning materials so teachers can be creative and innovate in learning process. The findings are initial information for future researchers in studying this problem in more or less the same context and issues